O rio Paraguai no megaleque do Nabileque, sudoeste do Pantanal mato-grossense, MS - Kuerten, Sidney [UNESP]; Assine, Mario Luis [UNESP] (My University, 2011)
The Nabileque fluvial fan is a Quaternary depositional system located along the southwestern border of the Pantanal, covering an area of approximately 9,100 km 2. It is a peculiar alluvial system because it is not associated with inflow from adjacent plateaus. The Nabileque megafan is formed by the Paraguay River at the exit of the Pantanal wetland, coalescing with the Pilcomayo megafan of the Chaco basin. A geomorphological zonation analysis was performed making use of remote sensing data with field verification. Most of the area is a vast alluvial plain made of Pleistocene deposits, whose surface is marked by the presence of an intricate network of distributary paleochannels. Areas blanketed by Pleistocene deposits are dissected by erosional streams and subject to frequent flooding events. The Paraguay River flows in a meander belt constrained by NE fractures associated with the Transbrasiliano Lineament, but deflects towards the SSE after the Negro River confluence composing the system's peripheral drainage. An abandoned meander belt is preserved within a remarkable N-S incised-valley that is interpreted as the ancient Paraguay River course. Processes of avulsion and river capture are suggested to explain the observed changes of the river course. The Nabileque River is an underfit stream within the incised-valley, cutting paleomeanders and point bars of the previous Paraguay River course.
The Paraguay River on the Nabileque fluvial megafan, southwest of the Pantanal wetland, Brazil
Keywords: Fluvial megafan; Incised-valley; Pantanal wetland; Paraguay River; Underfit stream